Medicinal plant-based drug delivery system for inflammatory bowel disease - Li, Ningcen; Wang, Meijuan; Lyu, Zhongxi; Shan, Kai; Chen, Zelin; Chen, Bo; Chen, Yong; Hu, Xiyou; Dou, Baomin; Zhang, Jingyu; Wang, Lifen; Zhao, Tianyi; et al. (Frontiers in Pharmacology, 2023)
Inflammatory bowel disease (IBD) is a chronic recurrent intestinal disease. The incidence rate of IBD is increasing year by year, which seriously endangers human health worldwide. More and more studies have shown that medicinal plants or their main phytochemicals have great potential in the treatment of intestinal diseases. However, the disadvantages of low oral absorption rate, low biological distribution and low systemic bioavailability limit their clinical application to a certain extent. In recent years, the application of nanotechnology has made it possible to treat IBD. Nanoparticles (NPs) drug delivery system has attracted special attention in the treatment of IBD due to its small size, low immunogenicity, surface modification diversity, targeting and other advantages. Synthetic nanoparticles and extracellular vehicles (EVs) can deliver drug components to colon, and play a role in anti-inflammation, regulation of oxidative stress, improvement of intestinal flora, etc. In addition, some medicinal plants can secrete EVs by themselves, and carry biological molecules with therapeutic effects to act on the intestine. Some clinical trials to evaluate the safety, tolerance, toxicity and effectiveness of EVs-loaded drugs in IBD are also progressing steadily. This review introduces that synthetic nanoparticles and medicinal plants derived EVs can play an important role in the treatment of IBD by carrying the effective active phytochemicals of medicinal plants, providing a scientific and reliable basis and perspective for further clinical application and promotion.